Inhibition of tumor growth by heparins in vivo (Hematology Meeting Reports, 2009)
Unfractionated Heparin (UFH) and its improved version LMWH are known to have poly-pharmacological activity at various levels. Earlier studies have focused on the plasma anti-Xa and anti-IIa pharmacodynamics (PD) of the different LMWH. Other important PD parameters for heparin and LMWH might explain the diverse clinical impacts of this class of agents in thrombosis and beyond. These diverse pharmacological actions include stimulation of the release of the vascular tissue factor pathway inhibitor (TFPI), inhibition of inflammation (via NFkappaB), inhibition of key matrix degrading enzymes, inhibition of platelet-cancer cell adhesion, and other mechanisms.